1976
DOI: 10.1152/jappl.1976.41.4.462
|View full text |Cite
|
Sign up to set email alerts
|

Plasma angiotensin II levels in hypoxic and hypovolemic stress in unanesthetized rabbits

Abstract: Plasma levels of angiotensin II were determined by radioimmunoassay in unanesthetized white rabbits exposed to acute hypoxia (FIO2 10% for 10 min), chronic hypoxia (0.5 atm up to 16 days), or hypovolemic stress (bleeding 20 ml/kg). Angiotensin II levels significantly decreased after 10 min of acute hypoxia in normal rabbits and significantly increased when the same procedure was applied to animals previously exposed to hypoxia by 6-8 days of permanence in the hypobaric chamber or sodium deprivation. Chronic hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 0 publications
5
31
0
Order By: Relevance
“…The increased cardiac output, however, presumably augments nutrient and 02 delivery to peripheral tissues, and hence may be beneficial. We and others (21,22) have also found a prompt decline in arterial AII concentrations in acutely hypoxic animals. These declines are associated with decreased systemic vascular resistance, having the effect ofreducing left ventricular afterload.…”
Section: Resultssupporting
confidence: 72%
“…The increased cardiac output, however, presumably augments nutrient and 02 delivery to peripheral tissues, and hence may be beneficial. We and others (21,22) have also found a prompt decline in arterial AII concentrations in acutely hypoxic animals. These declines are associated with decreased systemic vascular resistance, having the effect ofreducing left ventricular afterload.…”
Section: Resultssupporting
confidence: 72%
“…Fur- Table 1 Response to challenge with U-46619: Rise in mean pulmonary arterial pressure (PAP; mmHg) above baseline in response to U-46619 5 pg kg-' given as a bolus injection before and 5 min after intervention with saline or AT, receptor antagonist (Los, losartan; GR, GR138950C) thermore, there was a small increase in abundance of this receptor during the first week of exposure to hypoxia. This occurred in spite of evidence that circulating All levels increase during this time (Zakheim et al, 1976), a situation which might be expected to down-regulate All receptors. The increase in All binding sites does not appear to be part of a generalized cellular response to hypoxia; previous studies have reported no change in the density of vasointestinal polypeptide binding sites and the selective downregulation of the atrial natriuretic peptide clearance receptor in hypoxic rat lungs (Li et al, 1995;.…”
Section: Discussionmentioning
confidence: 80%
“…However, studies based on changes in All levels and angiotensin-converting enzyme (ACE) activity have failed to define its role. Circulating All levels have been reported to increase during the first week of exposure to hypoxia but thereafter decline to baseline (Zakheim et al, 1976). Several early studies indicated that whole lung ACE activity is reduced by chronic exposure to hypoxia (Keane et al, 1982;Kay et al, 1985;Jederlinic et al, 1988), but recently a local increase in ACE levels has been observed in the walls of newly muscularized pulmonary arteries in hypoxic rat lung (Morrell et al, 1995a).…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence support this hypothesis. First, chronic hypoxia has been reported to increase the ANG II circulating levels (42). Second, ANG II has been reported in vitro to increase the levels of AT 2 receptors through translational and not through transcriptional mechanisms (17).…”
Section: Discussionmentioning
confidence: 99%